The Histories of HIVs : The Emergence of the Multiple Viruses That Caused the AIDS Epidemics - Schneider, William H. (William Howard), 1945- (Book collections on Project MUSE., 2021)
"In this interdisciplinary collection, experts provide the most complete description to date of the often ignored and underappreciated features of the history of the multiple human immunodeficiency viruses (HIVs) responsible for the global AIDS pandemic"--